Biological Nitrogen Fixation in Sediments of a Cyanobacterial Bloom‐Occurring Bay in One Eutrophic Shallow Lake: Occurrence and Related Environmental Factors. Issue 10 (1st October 2021) - Tian, Linqi; Jiang, Helong; Bai, Leilei; Wang, Chunliu; Xu, Shengqi
Abstract: Biological nitrogen fixation (BNF) is an important source of bioavailable nitrogen in the aquatic environment that supports primary production. However, little is known about its occurrence and potential in eutrophic freshwater habitats. This study investigated the diazotrophic diversity and seasonal variation of nitrogenase activity (NA) in the sediments of a cyanobacterial bloom‐occurring bay of a freshwater lake. Sequencing analysis of the nif H gene revealed that diazotrophs in Clusters I and III constituted the dominant components of the diazotrophic community in Meiliang Bay. Both nif H and 16S rRNA gene sequencing indicated that the microbes in sediments have different community structures during the winter than during other seasons. The concentrations of dissolved sulfide, sulfate, and nitrate in pore water were significantly correlated with NA in sediments; however, the Mantel test indicated that dissolved sulfide had a more significant effect on the structure of the diazotrophic community than did other environmental factors. Laboratory culture experiments under different redox conditions further confirmed the inhibitory effect of dissolved sulfide on BNF in sediments. This study revealed that the BNF in sediments of Meiliang Bay was closely linked to variations in dissolved sulfide concentration, which has broadened our understanding of BNF in freshwater lakes. Plain Language Summary: The hypoxic environment formed by cyanobacterial blooms in eutrophic lakes and the rapid decomposition of dead cyanobacteria provide conditions for heterotrophic nitrogen fixation in sediments. Benthic biological nitrogen fixation can theoretically replenish nitrogen to the blooms in the water column. However, our understanding of the diversity of nitrogen‐fixing bacteria and the nitrogen‐fixing potential in freshwater lake sediments is very limited. Here, we explored the community structure and nitrogenase activity of nitrogen‐fixing bacteria in the sediments of a typical eutrophic lake. Our results showed that the nitrogen‐fixing microorganisms in the sediments were mainly heterotrophic Proteobacteria, and active nitrogen fixation occurred during the winter. The diazotrophic community structure and nitrogenase activity were significantly correlated with dissolved sulfide in pore water, and the high concentrations of sulfide during the summer may inhibit nitrogenase activity in sediments. Key Points: High diazotrophic diversity occurred in the sediments of a cyanobacterial bloom area in Lake Taihu The diazotrophic community and nitrogenase activity were correlated with dissolved sulfide in sediments Active sediment nitrogen fixation occurred in winter, nearly seven times as much as in summer